2016
DOI: 10.1039/c6ob00646a
|View full text |Cite
|
Sign up to set email alerts
|

Three-component oxysulfenylation reaction: two simple and convenient approaches to β-alkoxy sulfides

Abstract: An unprecedented method for the synthesis of β-alkoxy sulfides via a NaI/HBr-mediated three-component oxysulfenylation reaction of alkenes with arylsulfinic acids and alcohols is reported. Furthermore, I2-promoted oxysulfenylation of alkenes using sodium arylsulfinates instead of arylsulfinic acids to synthesise various β-alkoxy sulfides is also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…During the process, azides were converted to nitrogen radicals to get coupling with in situ generated carbon‐centered radicals. Lin and co‐workers [2d] elaborated the metal‐free oxysulfenylations by using simple alcohols as oxygen resource. A range of alcohols were smoothly applied in these transformations, and their steric hindrance had some effect on the yield.…”
Section: Sulfonyl Radical‐mediated Reactionsmentioning
confidence: 99%
“…During the process, azides were converted to nitrogen radicals to get coupling with in situ generated carbon‐centered radicals. Lin and co‐workers [2d] elaborated the metal‐free oxysulfenylations by using simple alcohols as oxygen resource. A range of alcohols were smoothly applied in these transformations, and their steric hindrance had some effect on the yield.…”
Section: Sulfonyl Radical‐mediated Reactionsmentioning
confidence: 99%
“…Along this line, the same research group also reported that in the presence of over-stoichiometric amounts of NaI and HBr, styrene derivatives 25 were similarly coupled with various aryl/alkyl-sulnic acids 26 and alkyl/benzyl-alcohols 27 to obtain b-alkoxy sulde products 28 with yields of up to 95% (Scheme 9b). 27 In 2018, Lei and co-workers developed an elegant electrochemical alkoxysulfenylation of alkenes 29 with thiols 30 and alcohols 31 under external oxidant-free conditions which exhibited better substrate scope compared to previously reported examples of this chemistry. 28 The reactions were conducted in an undivided cell under a constant current of 12 mA cm À2 with carbon anode and platinum plate cathode employing n Bu 4 NBF 4 as the electrolyte and MeCN as the solvent at 40 C, which afforded the b-alkoxy sulde products 32 in 20-95% yields (Scheme 10).…”
Section: Intermolecular Alkoxysulfenylation Of C-c Double Bondsmentioning
confidence: 99%
“… 13 In view of their significance, developing more practical and efficient synthetic approaches to construct these compounds is of great interest. 14 Two common methods are frequently utilized for the synthesis of vinyl sulfides, including the copper-catalyzed S -vinylation of thiols with vinyl halides and the addition of thiols to alkynes. 15 Recently, Zhang and co-workers reported a copper-mediated stereospecific C–H oxidative sulfenylation of terminal alkenes with disulfides.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Recently, Zhang and co-workers reported a copper-mediated stereospecific C–H oxidative sulfenylation of terminal alkenes with disulfides. 14 For the synthesis of vinyl sulfones, Wittig reaction of α-sulfinyl phosphonium ylides, β-elimination of halosulfones, condensation of aldehydes with sulfonylacetic, and the oxidation of the corresponding sulfides are perhaps the most common synthesis methods. 16 Recently, Zhan's group reported a copper( ii )-catalyzed chemo- and stereocontrolled synthesis of vinyl sulfones from terminal alkynes and arylsulfonyl hydrazides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation